PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS PREDICT-OBSERVE- EXPLAIN PADA PELAJARAN ILMU PENGETAHUAN ALAM KELAS IV - Dameis Surya Anggara; Candra Abdillah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aims to produce teaching materials in the form of Predict-Observe-Explain-based student worksheets in class IV science lessons the theme of Always Saving Energy is valid, practical, and effective in improving understanding of concepts. The research approach uses mixed methods with the Research and Development (R and D) methodology with procedures consisting of 4 steps namely 1) define, 2) design, 3) develope, 4) disseminate. Furthermore, the data collection instruments used questionnaire sheets for product validation by experts, teacher response questionnaire sheets, and items about understanding the concept of science. Data collected sequentially were analyzed using the Content Validity Index (CVI), Descriptive Statistics, and Independent Sample t Test. The results obtained are Predict-Observe-Explain student worksheets: 1) content valid criteria with a CVI value of 0.9, 2) good practicality criteria with a percentage of 79.56%, and 3) effective criteria in increasing understanding of the concept of Natural Sciences with evidence of a significant difference between an increase in the average understanding of the concept of experimental class science by 21.3750 higher than the increase in understanding of the concept of science in the control class of only 16.2500.